2017
DOI: 10.3390/w9010019
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bathymetric and LiDAR Data in Generating Digital Elevation Model over the Lower Athabasca River Watershed in Alberta, Canada

Abstract: Abstract:The lower Athabasca River watershed is one of the most important regions for Alberta and elsewhere due to fact that it counts for the third largest oil reserve in the world. In order to support the oil and gas extraction, Athabasca River provides most of the required water supply. Thus, it is critical to understand the characteristics of the river and its watershed in order to develop sustainable water management strategies. Here, our main objective was to develop a digital elevation model (DEM) over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
(21 reference statements)
1
10
0
1
Order By: Relevance
“…Our ultimate result shows both OK with anisotropic consideration (UK and OKA) and TPS (from RBF) interpolators have the best performance on the crosssectional data in LMR. This finding is similar to the conclusions from several above mentioned studies (Merwade, Maidment, and Goff 2006;Šiljeg, Lozić, and Šiljeg 2014;Chowdhury et al 2017;Chen et al 2018a). All these researches addressed that both geostatistical and deterministic interpolation methods have similar performance on generating bathymetric surface.…”
Section: Comparisons With Other Studiessupporting
confidence: 91%
See 3 more Smart Citations
“…Our ultimate result shows both OK with anisotropic consideration (UK and OKA) and TPS (from RBF) interpolators have the best performance on the crosssectional data in LMR. This finding is similar to the conclusions from several above mentioned studies (Merwade, Maidment, and Goff 2006;Šiljeg, Lozić, and Šiljeg 2014;Chowdhury et al 2017;Chen et al 2018a). All these researches addressed that both geostatistical and deterministic interpolation methods have similar performance on generating bathymetric surface.…”
Section: Comparisons With Other Studiessupporting
confidence: 91%
“…For example, Curtarelli et al (2015) found that lowest RMSE value was 0.92 m by using OK method for mapping the bathymetry of an Amazonian reservoir. Moreover, Chowdhury et al (2017) reported that RMSE value ranged between 0.48 and 0.67 m for both IDW and OKA methods in the lower Athabasca River, Canada. However, although the RMSE values in our study are greater than 1.7 m, which is higher than other study; the maximum depths and range are generally greater; therefore, this is in part a scale factor.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The system, MoRE (Modeling of Regionalized Emissions), also provides modelling capabilities to track pathway-specific emissions and river loads on a catchment scale and scenarios of emission reductions to be simulated. Accurate digital elevation models are also vital to the setup of geospatial models, an example of which is provided by Chowdhury et al [82] for the lower portion of the Athabasca River basin in Canada.…”
Section: Data Management For Geospatial Modellingmentioning
confidence: 99%